The role of bulk and interfacial morphology in charge generation, recombination, and extraction in non-fullerene acceptor organic solar cells. Issue 10 (17th September 2020) - Karki, Akchheta; Vollbrecht, Joachim; Gillett, Alexander J.; Xiao, Steven Shuyong; Yang, Yali; Peng, Zhengxing; Schopp, Nora; Dixon, Alana L.; Yoon, Sangcheol; Schrock, Max; Ade, Harald; Reddy, G. N. Manjunatha; et al.
Abstract : This study provides insight into the detailed bulk and interfacial morphological features critical in achieving high PCEs in polymer:NFA OSCs. Abstract : Some fundamental questions in the organic solar cell (OSC) community are related to the role of bulk and interfacial morphology on key processes such as charge generation, recombination, and extraction that dictate power conversion efficiencies (PCEs). The challenges with answering these questions arise due to the difficulty in accurately controlling, as well as comprehensively characterizing the morphology in bulk-heterojunction (BHJ) OSC blends. In this work, large variations in the interfacial and bulk morphologies of different low molecular weight fraction (LMWF) PM6:Y6 blends were detected despite the blends being fabricated from ostensibly the same building blocks. A drop in PCE from ∼15% to ∼5% was observed when the concentration of LMWFs of the PM6 polymer was increased from 1% to 52%. The drop in PCEs is found to be due to the lowering of the short-circuit current density ( J SC ) and fill-factor (FF) values as a result of compromised charge generation efficiencies, increased bulk trap densities, reduced charge transport, and inefficient charge extraction. The origin of the high device performance in the 1% LMWF blend is rationalized by the favorable bulk and interfacial morphological features, resolved from four techniques at sub-nanometer to sub-micrometer length scales. First, the closer donor:acceptor (D:A) interactions, smaller D and A domains, and increased D:A interfacial area facilitate ultrafast electron and hole transfer at the D:A interface. Second, the better long-range ordering and optimal phase separation of the D:A regions lead to superior charge transport and extraction.